AI enabled business : a smart decision kit - Stephens, Melodena; Vashishtha, Himanshu; Wagner, Dirk Nicolas (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"As the use of AI becomes more and more ubiquitous in companies around the world, managers charged with taking key decisions require resources to enable them to evaluate new projects effectively. The business case for AI projects is not necessarily clear cut and part of the reason for this is the lack of understanding on key decision criteria. AI touches on many ethical concepts - data privacy, validity and more importantly, its potential misuse. AI is often being used to replace human decision-making and there is often no real understanding of the implications of this. This book provides a detailed primer for practitioners without a deep technological background. It guides the reader through the basic issues and offers advice on 'how to take decisions'. There is a dearth of such books currently available and this book aspires to fill a growing niche"--